Increased depth of pancreas incisure on computed tomography as an independent predictor for T2DM - Yilong Huang; Zhangwaner Yao; Yongchun Zeng; Junjie Hua; Ning Yao; Zhixiao Luo; Zhibo Xiao; Qian Ge (Scientific Reports)
Abstract We aim to identify CT-based biomarkers in the pancreas for predicting both the presence and prognosis of T2DM. Between January and December 2021, a population of 2246 subjects undertaken health-check were recruited. Between January 2023 and June 2024, another 244 hospitalized patients with T2DM were recruited. Depth of pancreas incisure (DPI), CT attenuation, and thickness were measured using an unenhanced CT scan. Compared to individuals without T2DM, DPI was significantly increased in subjects with T2DM, regardless of whether they were of normal weight or obese. After adjusting for age, sex, BMI, waist circumference, lipid, liver function, and hepatic fat content, DPI remained independently associated with the presence of T2DM. However, no significant difference in DPI was observed between T2DM patients without insulin deficiency [Fasting C-peptide (FCP) ≥ 0.6 ng/ml] and those with absolute insulin deficiency (FCP < 0.6 ng/ml). DPI was not associated with the presence of absolute insulin deficiency; conversely, reduced pancreatic thickness was independently associated with this condition. Additionally, our findings did not reveal any significant association between pancreatic fat content and T2DM. Increased DPI may serve as a potential biomarker for predicting the risk of T2DM, whereas reduced pancreatic size may indicate a poorer prognosis for this disease.